Otitis Media in Fully Vaccinated Preschool Children in the Pneumococcal Conjugate Vaccine Era. (20th December 2017) - Talathi, Saurabh; Gupta, Neha; Sethuram, Swathi; Khanna, Shefali; Sitnitskaya, Yekaterina
Objectives. To evaluate the effect of pneumococcal conjugate vaccine (PCV13) on the burden of acute otitis media (AOM) and to evaluate the characteristics of AOM versus otitis media with effusion (OME) in the 2 PCV periods. Methods. A cohort of fully vaccinated children aged 18 to 60 months diagnosed with AOM from 2006 to 2015 was identified. Patients with otorrhea/bulging tympanic membrane were considered as true AOM, while those without bulging/otorrhea were considered to have OME. Burden of true AOM in the PCV7 and PCV13 periods and clinical features of true AOM versus OME were compared. Results. Of 393 episodes in our cohort, 50.8% occurred in PCV7 period. Burden of true AOM in the 2 PCV groups was similar: 26% in PCV7 versus 26.4% in PCV13 (odds ratio [OR] = 1.02, 95% confidence interval [CI] = 0.65-1.60). Factors significantly associated with OME were cold season (OR = 1.54, 95% CI = 1.04-2.4), fever (OR = 2.05, 95% CI = 1.29-3.3), and recurrence (OR = 2.24, 95% CI = 1.22-4.09). No complications of AOM were identified. Majority episodes were treated with antibiotics. Conclusion. Unlike the role of PCV13 in reducing invasive pneumococcal disease, its effect on reducing the burden of AOM is minimal as compared with PCV7. With regard to characteristics of AOM versus OME, findings of tympanic membrane should be used to suggest a diagnosis of AOM, instead of occurrence of fever or recurrence of AOM episodes. Using this approach would help in guiding the use of antibiotics appropriately.